Content design and validation of an instrument for the technical and tactical control of olympic wrestling - Agudelo Velásquez, Carlos Alberto (2020)
The purpose of this paper was to design and validate the contents of a tool that monitors the technical and tactical component in Olympic wrestling athletes, using related research projects and validation of expert judgment. The methodology applied consisted of accepting or rejecting contents, taking into account cut-off values (0.75) determined by the number of evaluators (8 subjects experts in the sport) and the rating scale recorded in the surveys (between 1 and 5) to assess the items (11 of the tool and 65 of contents), based on the validation of contents of an instrument, using Aiken’s V statistic. As a result, four out of 12 items of the instrument and seven elements of the contents (four of which were directly related to those rejected in the instrument) were eliminated. In conclusion, the design of a tool to observe, control, and determine the technical and tactical behavior of Olympic wrestlers is of great importance for all experts, but some contents must be removed or modified either because they are hard to understand or, according to experts, are not practical. The usefulness of a tool such as the one "approved" is inferred to support the preparation process of athletes.